Sosialisasi dan Pendampingan UMKM melalui Pembukuan Keuangan secara Digital menggunakan Aplikasi Teman Bisnis - Fitri, Lailatul Hidayah; Pramudya, Nanda Hari; Fatihah, Nazilatul; Pramudita, Dwi Anggi; Izzulhaq, Mohammad; Putri, Ferdiana; Priyanto, Moh. Wahyudi (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
Financial bookkeeping plays an important role in the management of micro, small and medium enterprises (MSMEs). Many MSMEs in West Klompang Village are not yet fully aware of the benefits and procedures for proper financial bookkeeping. Therefore, this community service aims to provide socialization and assistance with digital financial bookkeeping. The method involves observation, planning, implementation, and evaluation, with activities including interviews, outreach about the importance of bookkeeping, and introduction to the Business Friends application. As a result, there were 10 people who took part in this activity and showed high interest among MSME players in digital bookkeeping, with the Teman Bisnis application recognized as a practical tool for recording and analyzing financial transactions. The duration of this activity is 120 minutes with the hope that this service can improve the performance and welfare of MSMEs in West Klompang Village through regular and transparent financial bookkeeping.